Theoretical observation of the press as historical source - Hernández Ramos, Pablo (Historia y Comunicación Social, 2017)
This article focuses on the assessment of the newspaper as a flexible record of history. It analyses the unique look on reality that the newspaper offers, as an agent of the communication process, how the interest of this sources lays on its ideological bias, the difficult assessment of the state of public opinion and the similarities between the work of the journalist and that of the historian. As a conclusion, the importance of the press as historical source is stated, not only as a complement to official documents, but also fully valid as a primary source of historical research.